After the fact : - Davidson, James West (McGraw - Hill, 2000)
For more than twenty years, After the Fact has been a popular and best-selling approach to guiding students through American History and the methods used to generate it. In fifteen dramatic episodes that move chronologically through American history, this book examines such topics as oral evidence, photographs, ecological data, films and television programs, church and town records, census data, and novels.